The Impact of Climate Change on Income Handline Fishermen in Sorong City Southwest Papua - Loupatty, Ellen; Ratna, Ratna; Fahrizal , Ahmad; Sherly, Wa Ode (Agrikan Jurnal Agribisnis Perikanan, 2025)
Climate change has become one of the main challenges for the fisheries sector, especially for traditional fishermen such as handline fishermen in the city of Sorong, Southwest Papua. The phenomenon of rising sea temperatures, high waves, and seasonal uncertainty has led to a decrease in fishing days and a decline in catch yields, which directly affects the income of fishermen. This research aims to analyze the impact of climate change on the income of handline fishermen at the Fish Landing Base (PPI) Kaligi, Jembatan Puri. This research uses a descriptive quantitative approach with a survey method on handline fishermen. Primary data were collected through interviews and questionnaires, while secondary data were obtained from BMKG and the Department of Maritime Affairs and Fisheries. Data analysis was conducted using multiple linear regression to measure the influence of sea temperature (x1) and wave height (x2) on fishermen's income (y). The research results show that sea wave height has a negative and significant impact on fishermen's income, while sea temperature has a positive but not significant impact. The R-squared value of 0.582 indicates that 58.2% of the variation in fishermen's income is influenced by temperature and wave height. These results highlight the importance of adapting to climate change through the provision of weather information, climate literacy training, and the diversification of fishermen's livelihoods to enhance the economic resilience of coastal communities.